Immunomodulatory Properties and Molecular Effects in Inflammatory Diseases of Low-Dose X-Irradiation - Rödel, Franz; Frey, Benjamin; Manda, Katrin; Hildebrandt, Guido; Hehlgans, Stephanie; Keilholz, Ludwig; Seegenschmiedt, M. Heinrich; Gaipl, Udo S.; Rödel, Claus (Frontiers in Oncology, 2012)
Inflammatory diseases are the result of complex and pathologically unbalanced multicellular interactions. For decades, low-dose X-irradiation therapy (LD-RT) has been clinically documented to exert an anti-inflammatory effect on benign diseases and chronic degenerative disorders. By contrast, experimental studies to confirm the effectiveness and to reveal underlying cellular and molecular mechanisms are still at their early stages. During the last decade, however, the modulation of a multitude of immunological processes by LD-RT has been explored in vitro and in vivo. These include leukocyte/endothelial cell adhesion, adhesion molecule and cytokine/chemokine expression, apoptosis induction and mononuclear/polymorphonuclear cell metabolism and activity. Interestingly, these mechanisms display comparable dose dependences and dose-effect relationships with a maximum effect in the range between 0.3 - 0.7 Gy, already empirically identified to be most effective in the clinical routine. This review summarizes data and models exploring the mechanisms underlying the immunomodulatory properties of LD-RT that may serve as a prerequisite for further systematic analyses to optimize low-dose irradiation procedures in future clinical practice.